2023
DOI: 10.1142/s1088424623500700
|View full text |Cite
|
Sign up to set email alerts
|

Interactions of metronidazole and chloramphenicol with myoglobin: Crystal structure of a Mb-acetamide product

Abstract: Nitroorganics present a general concern for a safe environment due to their health hazards. However, some nitroorganics such as metronidazole (Mtz) and chloramphenicol (CAM) also possess medicinal value. Mtz and CAM can undergo reductive bioactivation presumably via their nitroso derivatives. We show, using UV-vis spectroscopy, that sperm whale myoglobin (swMb) and its distal pocket mutants retaining H-bonding capacity react with Mtz in the presence of dithionite to generate products with spectra suggestive of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…Reductive activation of RNO 2 to yield heme−RNO derivatives have also been described for some nitroorganics with cytochrome P450, 8,9 horse heart (hh) 10,11 and sperm whale (sw) 12 myoglobin (Mb), human hemoglobin (Hb), 10,13 and other heme proteins; 14−21 these heme−RNO derivatives were characterized by UV−vis spectroscopy. Importantly, it has been reported that human red blood cells possess sufficient reducing capacity for the metabolic conversion of various nitroorganics.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Reductive activation of RNO 2 to yield heme−RNO derivatives have also been described for some nitroorganics with cytochrome P450, 8,9 horse heart (hh) 10,11 and sperm whale (sw) 12 myoglobin (Mb), human hemoglobin (Hb), 10,13 and other heme proteins; 14−21 these heme−RNO derivatives were characterized by UV−vis spectroscopy. Importantly, it has been reported that human red blood cells possess sufficient reducing capacity for the metabolic conversion of various nitroorganics.…”
Section: ■ Introductionmentioning
confidence: 99%
“…[5] Recent studies have provided evidence that chloramphenicol exerts detrimental effects on both the structural integrity and functional properties of proteins, such as impeding the binding site of myoglobin. [6] Furthermore, molecular interactions between CHL and other biomolecules such as plasma proteins and bovine trypsin were also investigated. Thus, CHL exhibited a strong binding affinity towards these proteins, leading to disruption of their hydrogen bond network and subsequent alteration in folding.…”
Section: Introductionmentioning
confidence: 99%
“…It has been widely used to treat a variety of bacterial infections caused by susceptible strains, especially typhoid and paratyphoid, but also has certain hazards to humans and organisms [5] . Recent studies have provided evidence that chloramphenicol exerts detrimental effects on both the structural integrity and functional properties of proteins, such as impeding the binding site of myoglobin [6] . Furthermore, molecular interactions between CHL and other biomolecules such as plasma proteins and bovine trypsin were also investigated.…”
Section: Introductionmentioning
confidence: 99%